# SOLUTION: Please help The population of India is 1.13 billion people and is expected to double in 36 years. The population of China is 1.32 billion people and is expected to double in 67

Algebra ->  Algebra  -> Exponential-and-logarithmic-functions -> SOLUTION: Please help The population of India is 1.13 billion people and is expected to double in 36 years. The population of China is 1.32 billion people and is expected to double in 67       Log On

 Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help!

 Algebra: Exponent and logarithm as functions of power Solvers Lessons Answers archive Quiz In Depth

 Click here to see ALL problems on Exponential-and-logarithmic-functions Question 331896: Please help The population of India is 1.13 billion people and is expected to double in 36 years. The population of China is 1.32 billion people and is expected to double in 67 years. If the trends continue, when will the population of India be the same as China's? thanksAnswer by nerdybill(6948)   (Show Source): You can put this solution on YOUR website!The population of India is 1.13 billion people and is expected to double in 36 years. The population of China is 1.32 billion people and is expected to double in 67 years. If the trends continue, when will the population of India be the same as China's? . You will be applying the "exponential growth" formula: N = Noe^(rt) where N = population at time t No = initial population r = constant (this what we need to find for India and China) t = time . India: 2(1.13) = 1.13e^(r*36) 2 = e^(r*36) ln(2) = r*36 ln(2)/36 = r Equation of growth for India: N = 1.13e^(ln(2)t/36) . China: 2(1.32) = 1.32e^(r*67) 2 = e^(r*67) ln(2) = r*67 ln(2)/67 = r Equation of growth for China: N = 1.32e^(ln(2)t/67) . Set them equal and solve for t: 1.13e^(ln(2)t/36) = 1.32e^(ln(2)t/67) take the ln of both sides: ln(1.13e^(ln(2)t/36)) = ln(1.32e^(ln(2)t/67)) ln(1.13) + ln(2)t/36) = ln(1.32) + ln(2)t/67) ln(2)t/36) - ln(2)t/67) = ln(1.32) - ln(1.13) t(ln(2)/36) - ln(2)/67) = ln(1.32) - ln(1.13) t = (ln(1.32)-ln(1.13))/(ln(2)/36) - ln(2)/67) t = 17.45 years